Lymph node metastasis prediction of papillary thyroid carcinoma based on transfer learning radiomics - Jinhua Yu (Nature Portfolio, 2020)
A non-destructive and efficient method for predicting the risk of lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC) patients is highly needed. Here, the authors develop a transfer learning radiomics model for preoperative prediction of LNM in patients with PTC in a multicenter scenario.